Insurance Management. - Sahoo, S. C. (Global Media, 2008)
Understanding Risk ManagementIntroduction to InsurancePrinciples of Insurance ContractHistory and Development of InsuranceIntroduction to Life InsuranceMortality TablesPremium and BonusPolicy ConditionsLife Insurance ProductsAnnuitySettlement of ClaimsULIP and Pension PlansLife Insurance Corporation of India (LlC)Introduction to Fire InsurancePrinciples of Fire InsuranceFire Insurance PoliciesSettlement of Claim in Fire InsuranceIntroduction to Marine InsuranceMarine Insurance PoliciesClauses in Marine PoliciesPremium FixationMarine Losses and Claim SettlementTariff Advisory CommitteeRegistration of Insurance CompanyProtection of Policyholders' InterestMarketing of Insurance ProductsIRDA Rules and Regulations Governing AdvertisementsBancassuranceReinsuranceLoss Prevention and ControlHealth InsuranceAgriculture InsuranceAccident and Auto InsuranceMicro InsuranceTerrorism, Kidnap and Ransom InsuranceProperty InsuranceLiability InsuranceCritical Illness InsuranceRural and Social Sector RegulationsUnderwritingTax Aspects of InsuranceInsurance Need AnalysisInsurance and Information TechnologyCompetitive EnvironmentAnnexuresCasesSpecimen Copies of Forms and PoliciesSelect BibliographyGlossary on InsuranceSubject Index.